Influence of Foliar Applications of Synthetic Compounds on Wheat Grain Quality During Terminal Heat Stress - Singh, Tribhuwan; Singh, Chandrakant; C.V., Nandeesha; Pansuriya, A.G. (Journal of Cereal Research, 2025)
Wheat (Triticum aestivum L.) plants in many locations of the world face terminal high temperature stress during the grain filling stage, which is a major contributor to a decrease in single seed weight and texture and, as a result, a reduction in grain quality and yield. To mitigate terminal heat stress of wheat strategies are followed like foliar application of nitrogenous compound, polyamines, sulfhydryl compounds and different osmoprotectants. The influence of foliar applied exogenous osmoprotectants on terminal heat stress in wheat (Triticum aestivum L.) was investigated in the current study under field conditions and it also alter quality of grain. Synthetic osmoprotectants shows varying results on different quality attributes. Like protein content increases in compared to control when SNP (400μg/ml and 800μg/ml) and DTT (50ppm) applied at different concentration while for starch, moisture content, sedimentation value and hectolitre weight best results were observed in thiourea (20mM and 40mM) and KNO3 (1%) treatment. Same as KNO3 and DTT increases gluten content of the grains.